Visceral obesity enhances inflammatory response after laparoscopic colorectal resection. Issue 11 (15th September 2021) - Conti, Cristian; Pedrazzani, Corrado; Turri, Giulia; Gecchele, Gabriele; Valdegamberi, Alessandro; Ruzzenente, Andrea; Zamboni, Giulia A.; Lippi, Giuseppe; Guglielmi, Alfredo
Abstract: Aims: C‐reactive protein (CRP) is used for monitoring postoperative inflammation (POI) and detecting infectious complications. The aim of this study was to assess the effect of visceral obesity (VO) on acute POI measured through CRP after elective laparoscopic colorectal resection. Methods: Pre‐operative Computed tomography images of 357 patients who underwent laparoscopic colorectal resection were analyzed. Visceral adipose tissue (VAT) area was measured for each patient. VO was defined as VAT area >163.8 cm 2 in men and >80.1 cm 2 in women according to accepted sex‐specific cut‐offs. Postoperative outcomes and CRP values were compared between VO and non‐VO groups. The most appropriate CRP value for identifying infectious complications in the two groups was assessed with receiver operating characteristic (ROC) curves. Univariate and multivariate analyses were conducted for factors affecting POI including VO. Results: No differences in postoperative outcomes and infectious complications were found in VO patients (62.2% of the overall population). Both in the overall cohort and in patients without infectious complications, VO was associated with higher CRP values on postoperative day (POD) 1, POD2, POD3, and POD5. A positive correlation was found between VAT and CRP on all PODs. VO independently predicted higher CRP on POD1‐3 in patients without infectious complications but not in those who developed complications. ROC curves analysis showed optimal accuracy for detection of infectious complications for CRP on POD3 in both groups, though the optimal cut‐off value was higher in VO group (154 vs 136 mg/L). Conclusions: VO is not associated to increased complications after laparoscopic colorectal resection. Nevertheless, it is independently associated to higher CRP in the overall population and in patients without infectious complications. Consequently, CRP values on POD3 higher than cut‐offs commonly adopted in the clinical practice should be carefully evaluated in VO patients to assess the occurrence of infectious complications.